Russian and Tatar Languages in Official Internet-Resources - Mahmutov, Zufar Aleksandrovich; Sagitova, Alfiya Galeevna; Ibragimova, Elmira Rashitovna (International Review of Management and Marketing, 2015)
The article deals with the study of official segment of national, Tatar, Internet sector. Two parts can be distinguished there: theoretical and practical. The first part provides the definition of minority Internet, which underlines its dichotomous nature, the websites of Tatnet (Tatar Internet), proceeding from the functional purpose of digital resources; the segments are provided (official, media, cognitive, social), the types of relations between the language contents are distinguished (main, parity, slightly inferior, secondary, nominal). The practical part contains the results of complex linguistic monitoring of 317 websites of official segment of national Tatar Internet, that took place in June of 2014; it provided a conclusion, that, at present, the status of Tatar language in the Internet-space is out of line with the status of state language of the Tatarstan Republic and needs more efficient support measures and the purposeful policy, aimed at consolidation of its positions. Keywords: minority Internet, ethnic language, language content, network resource, official Internet segment, informative, Tatar language, public sector, commercial sector, state language. JEL Classifications: D83; O33; O21; Z13